2001
DOI: 10.1128/jcm.39.6.2126-2133.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Pneumocystis carinii from 18 Primate Species Confirms Host Specificity and Suggests Coevolution

Abstract: Primates are regularly infected by fungal organisms identified as Pneumocystis carinii. They constitute a valuable population for the confirmation of P. carinii host specificity. In this study, the presence of P. carinii was assessed by direct examination and nested PCR at mitochondrial large subunit (mtLSU) rRNA and dihydropteroate synthetase (DHPS) genes in 98 lung tissue samples from captive or wild nonhuman primates. Fifty-nine air samples corresponding to the environment of different primate species in zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 38 publications
(30 reference statements)
9
114
0
4
Order By: Relevance
“…To quote Hudson andCoyne (2002, p. 1557), a species recognized by GSC is a ''basal, exclusive group of organisms, whose members are all more closely related to each other than they are to any organisms outside the group, and that contains no exclusive group within it.'' In all cases in which the PSC has been used to describe species of global isolates of a morphological fungal species, cryptic species have been recognized, for example within Schizophyllum commune (James et al 1999), Sclerotinia sclerotiorum (Carbone and Kohn 2001a) and outbreeding Neurospora species (Dettman et al 2003b) (and see also Demanche et al 2001;Fisher et al 2002;Franzot et al 1999;Kasuga et al 2003;Koufopanou et al 1997;Sullivan et al 1995;Xu et al 2000). BSR and PSR have been compared for species of Neurospora and the biological species recognized by success in mating tests are nearly the same as the phylogenetic species described by the concordance of multiple gene genealogies (Dettman et al 2003a); the two species concepts are effectively congruent.…”
Section: Species Recognitionmentioning
confidence: 99%
“…To quote Hudson andCoyne (2002, p. 1557), a species recognized by GSC is a ''basal, exclusive group of organisms, whose members are all more closely related to each other than they are to any organisms outside the group, and that contains no exclusive group within it.'' In all cases in which the PSC has been used to describe species of global isolates of a morphological fungal species, cryptic species have been recognized, for example within Schizophyllum commune (James et al 1999), Sclerotinia sclerotiorum (Carbone and Kohn 2001a) and outbreeding Neurospora species (Dettman et al 2003b) (and see also Demanche et al 2001;Fisher et al 2002;Franzot et al 1999;Kasuga et al 2003;Koufopanou et al 1997;Sullivan et al 1995;Xu et al 2000). BSR and PSR have been compared for species of Neurospora and the biological species recognized by success in mating tests are nearly the same as the phylogenetic species described by the concordance of multiple gene genealogies (Dettman et al 2003a); the two species concepts are effectively congruent.…”
Section: Species Recognitionmentioning
confidence: 99%
“…One explanation for these observations is that Pneumocystis is an obligate parasite which has co-evolved in a particular host in order to survive. 9 The above data further indicate that human Pneumocystis infection is not a zoonosis. DNA sequence analysis of human Pneumocystis at several different loci has demonstrated genetic diversity in the organism 7 10 11 and has shown that two or more types of organism infect some patients with Pneumocystis pneumonia.…”
Section: Yet Ifmentioning
confidence: 87%
“…De nos jours, la pneumocystose reste [10]. De plus, les études récentes sur la coévolution des Pneumocystis et de leurs hôtes témoignent de l'adaptation très ancienne de ces parasites aux mammifères [11,12]. Ainsi, le genre Pneumocystis regroupe des populations génétiquement isolées, qui ont subi un long processus d'adaptation à chaque espèce de mammifère, entraînant une spé-ciation [10].…”
Section: Pneumocystis Et Pneumocystose Aujourd'huiunclassified